THE INFLUENCE OF SMARTPHONES ON BEHAVIOR SEXUAL TEENAGE IN HUTAGAOL VILLAGE PEATALUN, BALIGE DISTRICT TOBA DISTRICT YEAR 2022THE INFLUENCE OF SMARTPHONES ON BEHAVIOR SEXUAL TEENAGE IN HUTAGAOL VILLAGE PEATALUN, - Monalisa; Herna Rinayanti Manurung; Lidya Natalia Sinuhaji; Nofita Rifka Br Meliala; Nurul Sari Pazira, (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Background :Smartphone is one of the information technology or mobile phones which are often called smart phones. Smartphones provide easy free access and social media services. As a result of the negative impact of smartphones, it is easy for teenagers to access porn/sex media, resulting in deviant sexual behavior. Destination :This study aims to analyze the influence of smartphones on sexual behavior in adolescents in Hutagaol Peatalun Village, Balige District, Toba Regency. Method:the type of research used is descriptive analytic. With a cross sectional approach method with a sample size of 35 people and the sampling technique used is the Sloving . formula Results :The influence of smartphones on adolescent sexual behavior was obtained value = 0.000 (α < 0.05). Conclusion :the influence of smartphone use with adolescent sexual behavior.